Multiview-Video-Plus-Depth Coding Based on the Advanced Video Coding Standard - Hannuksela, Miska M.; Gabbouj, Moncef; Rusanovskyy, Dmytro; Su, Wenyi; Chen, Lulu; Li, Ri; Aflaki, Payman; Lan, Deyan; Joachimiak, Michal; Li, Houqiang (IEEE transactions on image processing, 2013)
This paper presents a multiview-video-plus-depth coding scheme, which is compatible with the advanced video coding (H.264/AVC) standard and its multiview video coding (MVC) extension. This scheme introduces several encoding and in-loop coding tools for depth and texture video coding, such as depth-based texture motion vector prediction, depth-range-based weighted prediction, joint inter-view depth filtering, and gradual view refresh. The presented coding scheme is submitted to the 3D video coding (3DV) call for proposals (CfP) of the Moving Picture Experts Group standardization committee. When measured with commonly used objective metrics against the MVC anchor, the proposed scheme provides an average bitrate reduction of 26% and 35% for the 3DV CfP test scenarios with two and three views, respectively. The observed bitrate reduction is similar according to an analysis of the results obtained for the subjective tests on the 3DV CfP submissions.